Lark: As a Medium of Interpersonal Communication for TNS Employees to Manage Work Stress Amidst the Covid-19 Pandemic - Pratiwi, Gebby Septia Akhdev; Witono, Andika (Journal of Communication and Public Relations, 2024)
Working from home (WFH) during the community activity restrictions period (PPKM), such as those imposed by Indonesia’s government, leaves employees with little choice in dealing with work stress. Lark is a collaborative working media tool, during work from home all communication in TNS department took place in Lark. This study's importance is to see how Lark basically a formal working media tool can form an interpersonal communication between woman employees that help them to manage work stress during WFH and PPKM period. Since the trend of working from home is likely to continue even after pandemic, this research provides contribution and information related to communication tools and work from home consequences. The theory for this research is Computer-mediated Communication and Social Information Processing Theory (SIPT). This research method employs a qualitative approach through participant observation, in-depth interviews, and library study. This study finds that implementing WFH during the Covid-19 period resulted in heightened work stress among female employees in TNS Department. It was observed that sharing work-related burdens with coworkers proved to be effective in reducing work stress. Interestingly, sharing with a coworker was considered more beneficial than sharing with a spouse or family. Lark application which serves as a working media tool turns out can facilitate interpersonal communication among female employees. The application's instant messenger, phone call, and expressive emoji make it convenient for employees to share their concerns and stress, as compared to using video conferences.